Объяснение:
(х+4)(х+3)(х+2)(х+1)-120=0 ;
групуємо множники так :
[(х+4)(х+1)] [(х+3)(х+2)] - 120 = 0 ;
( x² + 5x + 4 )( x² + 5x + 6 ) - 120 = 0 ;
позначимо x² + 5x + 4 = у , тоді
у * ( у + 2 ) - 120 = 0 ;
y² + 2y - 120 = 0 ; D = 484 > 0 ; y₁ = - 12 ; y₂ = 10 .
Маємо два простих рівняння :
x² + 5x + 4 = - 12 ; x² + 5x + 4 = 10 ;
x² + 5x + 16 = 0 ; x² + 5x - 6 = 0 ;
D = - 39 < 0 ; D = 49 > 0 ;
xЄ ∅ ; x₁ = - 6 ; x₂ = 1 .
В - дь : - 6 і 1 .
√x=t
t²-6t=0
t(t-6)=0
t-6=0 или t=0
t=6
√x=t
√x=6
√36=6
х1=36
х2=0
ответ; 0; 36